Socio-Educational Challenges of Communities Treating Young People in Conflict with the Law. Motivation and Good Practices of Instruction and Institutional Management. Two Cases from Mexico - Acevedo-Rodríguez, Carlos (Revista Electrónica Educare, 2020)
In Mexico, adolescents who have had conflicts with the law and have been tried and sentenced to serve time in freedom or confinement must attend or live in institutions called communities. In these spaces, a variety of activities, such as psychological therapies, artistic and labor workshops, and classes are carried out as part of young people’s rehabilitation. In 2016, the National Law of the Comprehensive Criminal Justice System for Adolescents was enacted (Cámara de Diputados de H. Congreso de la Unión, 2016). The objective is to move from a treatment based on a punitive model to a strategy based on socio-educational improvements. Currently, there is not enough information about how the communities are adapting to the new guidelines, specifically regarding best practices of instruction and institutional management. This scientific paper shows the results of the qualitative analysis of two communities located in the central zone of Mexico. Through interviews with thirty young people serving their sentences under the new law, interviews and discussion groups with twenty institutional officials, and observation of socio-educational activities, the profiles of youths in these communities and best practices were identified. It was found that despite several problems and disadvantages of young people, the best practices identified have a positive impact on the motivation of young people and officials. To illustrate this process, an analytical framework about the influence of motivation on learning and management was constructed. Finally, we state that every person has the best capacity to learn in social environments which are able to stimulate motivation; we also propose areas of improvement.